The Indonesian Confix /Pe-+-an/ in Thammasat University Student Descriptive Text: Allomorph, Usage, and Grammatical Meaning - Mukhibun, Akhmad; Saddhono, Kundharu (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2023)
The Indonesian language program for foreign speakers (BIPA) has been taught in 52 countries with a total of 154 thousand students by 2023. With this high number of students, Indonesian is expected to spread and become an international language by 2045. Even though Indonesian is relatively easy to learn, BIPA students are suspected to have difficulty mastering the rules of affixation/additions in forming Indonesian vocabulary. This research aims to explain (1) the confix allomorph /pe-+-an/ in BIPA students' descriptive texts. (2) use of the confix /pe-+-an/. (3) grammatical meaning formed due to the attachment of the /pe-+-an/ confix. This research is a descriptive qualitative research with a content analysis approach design. The data source used is a descriptive text document of BIPA students from Thammasat University, Thailand. Validity test uses triangulation of data sources and theory. The results of the research show (1) there are six variations of the confix allomorph /pe-+-an/, namely /pe-+-an/, /pem-+-an/, /pen-+-an/, /peng-+-an /, /peny-+-an/, /penge-+-an/. (2) The use of the confix /pe-+-an/ in BIPA students' descriptive texts was found in 32 data. The function of attaching the confix /pe-+-an/ is to nominalize verbs, adjectives, nouns and number words. (3) The grammatical meaning that appears, for example, regarding leaving (travel), things that are done (work), organizations that conduct business (companies), processes, actions, ways of saying (pronunciation).